If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6n + -6 = 2n + -2 Reorder the terms: -6 + 6n = 2n + -2 Reorder the terms: -6 + 6n = -2 + 2n Solving -6 + 6n = -2 + 2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2n' to each side of the equation. -6 + 6n + -2n = -2 + 2n + -2n Combine like terms: 6n + -2n = 4n -6 + 4n = -2 + 2n + -2n Combine like terms: 2n + -2n = 0 -6 + 4n = -2 + 0 -6 + 4n = -2 Add '6' to each side of the equation. -6 + 6 + 4n = -2 + 6 Combine like terms: -6 + 6 = 0 0 + 4n = -2 + 6 4n = -2 + 6 Combine like terms: -2 + 6 = 4 4n = 4 Divide each side by '4'. n = 1 Simplifying n = 1
| -7(x+2)=-5(x-2) | | -7(4g-6)+14g=-11g | | 4w+11=79 | | -5+-3-4= | | 100x-10x=2 | | 2x+3=2x-4 | | 100x-x=2 | | 4+(-8+s)=20 | | 2=7-2n+7n | | 5x-10+4x-17=41 | | -(x+7)=11 | | -10p-8=8(6p-5)+10(2+4p) | | 5(3s+6)=90 | | 78=-10+8r | | 11h+-13h+-13=9 | | 26=5u-9 | | x^2-x-e=0 | | 4y+10=13y | | 2x-y=5.5 | | -7h-4h+-14=19 | | 4-3y=2y+1 | | 3w-10=47 | | 100x-10=12 | | 2/3(h-27)=6-2/3h | | 7(x+2)+8(x+2)=5x-5 | | (e+5)*2=21 | | 5v+17=67 | | -1x-29=13x+2x | | 7a-15=34 | | -1.6(2c+12)=12 | | -x+6x+7=0 | | -12v=96 |